An adaptive IgA‐BEM with hierarchical B‐splines based on quasi‐interpolation quadrature schemes. (5th December 2018) - Falini, Antonella; Giannelli, Carlotta; Kanduč, Tadej; Sampoli, Maria Lucia; Sestini, Alessandra
Summary: The isogeometric formulation of the boundary element method (IgA‐BEM) is investigated within the adaptivity framework. Suitable weighted quadrature rules to evaluate integrals appearing in the Galerkin BEM formulation of 2D Laplace model problems are introduced. The proposed quadrature schemes are based on a spline quasi‐interpolation (QI) operator and properly framed in the hierarchical setting. The local nature of the QI perfectly fits with hierarchical spline constructions and leads to an efficient and accurate numerical scheme. An automatic adaptive refinement strategy is driven by a residual‐based error estimator. Numerical examples show that the optimal convergence rate of the Galerkin solution is recovered by the proposed adaptive method.